Marketing research and strategic marketing plan: Lisbon art weekend: Lisbon Art Weekend Internship Report - Gurler, Engin Deniz (2021)
Internship Report presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence